2021
DOI: 10.1249/mss.0000000000002617
|View full text |Cite
|
Sign up to set email alerts
|

Health Outcomes after Pregnancy in Elite Athletes: A Systematic Review and Meta-analysis

Abstract: This study aimed to evaluate postpartum maternal health and training outcomes of females who were competing or training as elite athletes before or during pregnancy. Methods: Online databases were searched up to August 26, 2020. Studies of any design and language were eligible if they contained information on the relevant population (postpartum athletes [any period after pregnancy]), exposure (engaged in the highest level of sport immediately before or during pregnancy), comparators (sedentary/active controls)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 38 publications
0
43
1
Order By: Relevance
“…Eighteen athletes from nine Olympic sports (team and individual, winter and summer games) participated in this research. Between January and June 2021, we recruited postpartum elite athletes through social media (i.e., Twitter, Facebook, Instagram) and word of mouth via a purposeful and snowball sampling approach [ 10 ]. To be eligible, athletes could reside anywhere in the world, had to be ≥ 18 years old, and must have trained and/or competed at the highest level of their sport immediately prior to, and during, pregnancy, and returned to sport following childbirth within the last 5 years (2016–2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eighteen athletes from nine Olympic sports (team and individual, winter and summer games) participated in this research. Between January and June 2021, we recruited postpartum elite athletes through social media (i.e., Twitter, Facebook, Instagram) and word of mouth via a purposeful and snowball sampling approach [ 10 ]. To be eligible, athletes could reside anywhere in the world, had to be ≥ 18 years old, and must have trained and/or competed at the highest level of their sport immediately prior to, and during, pregnancy, and returned to sport following childbirth within the last 5 years (2016–2021).…”
Section: Methodsmentioning
confidence: 99%
“…These statements strongly demonstrate of the paucity of data supporting safe return to sport. More recently, we conducted an updated systematic review of the literature that demonstrated elite athletes were more likely than sub-elite and recreational athletes to return to training in the first 6× weeks after delivery [ 10 ]. Participants also experienced increased rates of injury, likely exacerbated by a rapid return to sport, further illustrating the urgent need to have strong supports and return to training plans for elite athletes.…”
Section: Introductionmentioning
confidence: 99%
“…The runner may begin running at any time postpartum if they have been medically cleared and screened for running readiness (Figure 1), as recent literature suggests that early return to exercise does not negatively impact pelvic health outcomes or increase injury risk in athletes. 73,74 Symptoms should be continuously monitored and addressed by the health care team. As each individual may have unique pregnancy and postpartum experiences, this framework should be used to assist each runner in achieving their running goals.…”
Section: How To Use the Frameworkmentioning
confidence: 99%
“…Amateur athletes tend to return to exercise less quickly than those at the elite level. 27 The key is to start gentle walking a few days after hospital discharge and to gradually increase the amount and intensity of walking. She was advised that trying to 'bridge' from walking to running is safest (ie progressing from challenging walking, including hills and at a brisk pace, to very easy running), which she managed to do at week 10 after giving birth.…”
Section: Case Studies Casementioning
confidence: 99%